Blockade of the PD-1/PD-L1 Immune Checkpoint Pathway Improves Infection Outcomes and Enhances Fungicidal Host Defense in a Murine Model of Invasive Pulmonary Mucormycosis - Wurster, Sebastian; Albert, Nathaniel D.; Bharadwaj, Uddalak; Kasembeli, Moses M.; Tarrand, Jeffrey J.; Daver, Naval; Kontoyiannis, Dimitrios P. (Frontiers in Immunology, 2022)
Anecdotal clinical reports suggested a benefit of adjunct immune checkpoint inhibitors (ICIs) to treat invasive mucormycosis. However, proof-of-concept data in animal models and mechanistic insights into the effects of ICIs on host defense against Mucorales are lacking. Therefore, we studied the effects of PD-1 and PD-L1 inhibitors (4 doses of 250 µg/kg) on outcomes and immunopathology of invasive pulmonary mucormycosis (IPM) in cyclophosphamide- and cortisone acetate-immunosuppressed mice. Rhizopus arrhizus-infected mice receiving either of the ICI treatments had significantly improved survival and less morbidity compared to isotype-treated infected mice. While early improvement of morbidity/mortality was comparable between the ICI treatments, anti-PD-L1 provided more consistent sustained protection through day 7 post-infection than anti-PD-1. Both ICIs enhanced the fungicidal activity of ex-vivo splenocytes and effectively counteracted T-cell exhaustion; however, macrophages of ICI-treated mice with IPM showed compensatory upregulation of other checkpoint markers. Anti-PD-1 elicited stronger pulmonary release of proinflammatory cytokines and chemokines than anti-PD-L1, but also induced cytokines associated with potentially unfavorable type 2 T-helper-cell and regulatory T-cell responses. Although no signs of hyperinflammatory toxicity were observed, mice with IPM receiving ICIs, particularly anti-PD-1, had elevated serum levels of IL-6, a cytokine linked to ICI toxicities. Altogether, inhibition of the PD-1/PD-L1 pathway improved clinical outcomes of IPM in immunosuppressed mice, even without concomitant antifungals. PD-L1 inhibition yielded more favorable immune responses and more consistent protection from IPM-associated morbidity and mortality than PD-1 blockade. Future dose-effect studies are needed to define the “sweet spot” between ICI-induced augmentation of antifungal immunity and potential immunotoxicities.